What’s The Beef? Current Trends of the Florida Beef Cattle Industry as Perceived by Florida Beef Cattle Industry Leaders - Michah Gallagher; Matt Benge; Lauri Baker (Journal of Human Sciences and Extension)
Agriculture plays a vital role in Florida’s economy, as it is the second largest industry behind tourism. Additionally, Florida is a leading cow-calf production state in the United States which is impacted by numerous factors internal and external to the industry itself. The Theory of Reasoned Action was used to explore current trends of the Florida beef cattle industry as perceived by Florida cattle industry leaders. Thirteen themes emerged from the data, such as environmental protection and alternative proteins. Florida ranchers need support from government entities to continue participation in conservation, education, and improvement of the cattle industry in Florida. Recommendations are for producers to advocate for both their own farms and the state by sharing more of their ‘story’ with consumers and government entities.